Love is a many trousered thing : confessions of Georgia Nicolson 8 - Rennison, Louise (Confessions of Georgia Nicolson, 2008)
In a series of diary entries, British teenager Georgia Nicolson describes her continuing romantic woes as she is pushed toward a decision about the three boys in her life.